EVALUASI PELAKSANAAN MANDATORY TRAINING ONLINE DENGAN MODEL KIRKPATRICK PADA HOLIDAY INN RESORT NUSA DUA - INJELINA, NI KADEK IRMA; ARTATANAYA, I GUSTI LANANG SUTA; ADNYANA, IDA BAGUS ARTHA (Universitas Mahasaraswati K. Mataram, 2024)
Abstrak This study aims to obtain an overview of the implementation of Mandatory Online Training based on Kirkpatrick's Evaluation Models at the Holiday Inn Resort Bali Nusa Dua. Data were collected through the distribution of questionnaires and analyzed using quantitative descriptive techniques. The questionnaires were given to permanent and contract employees, excluding daily workers or trainees who participated in this training. The sample in this study was taken using proportionate stratified random sampling techniques. The results of this study at the reaction level showed that the training was conducted well, with an overall average reaction level dimension of 4.10 on a scale of 5.00. At the learning level, the results were very good with an average score of 4.16 on a scale of 5.00. The behavior level of the training participants, measured at the behavior level, showed good results with an overall average behavior level dimension of 4.12 on a scale of 5.00. Overall, the average result level obtained a good criterion with an average score of 4.15 on a scale of 5.00.